2022
DOI: 10.21303/2585-6847.2022.002671
|View full text |Cite
|
Sign up to set email alerts
|

Lexicon-based sentiment analysis of medical data

Abstract: The article explores the possibilities of applying sentiment analysis for the use of information collected in the medical social media environment in medical decision-making. Opinions and feedbacks of medical social media subjects (physician, patient, health institution, etc.) make media resources an important source of information. The information collected in these sources can be used to improve the quality of health care and make decisions, taking into account the public opinion. Researches in this field ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In [17], the possibilities of applying lexicon-based sentiment analysis (SA) for the use of information collected in the medical social media environment in medical decision-making are explored. It is shown that with the SA of information obtained from crowdsourcing in medical media resources, more objective and transparent decision-making can be achieved that takes into account public opinion for solving a certain medical problem.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In [17], the possibilities of applying lexicon-based sentiment analysis (SA) for the use of information collected in the medical social media environment in medical decision-making are explored. It is shown that with the SA of information obtained from crowdsourcing in medical media resources, more objective and transparent decision-making can be achieved that takes into account public opinion for solving a certain medical problem.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…referring to the statistical analysis of the surveys collected in the doctor-patient segment of medical social media and the demographic (location, gender, age) indicators of e-patients. [17] explores the possibilities of applying sentiment analysis (SA) for the use of information obtained from crowdsourcing in medical social media resources in medical decision-making, and indicates that the application of such an approach to solving a certain medical problem «public opinion», «mass opinion» ensures more objective and transparent decisions.…”
Section: Introductionmentioning
confidence: 99%